CHANGES IN MORPHODENSITOMETRIC PARAMETERS OF THE PARAVENTRICULAR NUCLEUS OF THE HYPOTHALAMUS IN RATS UNDER STRESS OF DIFFERENT DURATIONS - І. Федоряк; Р. Булик (Неонатологія, хірургія та перинатальна медицина)
Paraventricular nuclei of the hypothalamus play the important role in both endocrine regulation of the tropic function of the adenohypophysis and the organism's neuroendocrine response to stress of various origins, particularly sustained photoperiod disturbances. However, morphodensitometric properties of the medial parvocellular subnuclei within the rat hypothalamic paraventricular nuclei across varying photoperiod durations have yet to be investigated.